Needs Analysis of English Language Competencies for Prospective Islamic Religious Education (PAI) Teachers in Islamic Higher Education: English - Moh. Zainol Kamal; Ukhtul Iffah; Ahmad Effendi; Moh. Wardi; Hodairiyah; Nufil Indriyani (JOEY: Journal of English Ibrahimy, 2026)
This study analyzed the English language competency needs of prospective Islamic Religious Education (PAI) teachers in Islamic higher education institutions. The study was conducted at STIT Aqidah Usymuni Sumenep as the research site, and the informants included lecturers, students, and alumni. This study employed a qualitative approach with a case study design to describe the English language competency needs of prospective PAI teachers in Islamic higher education institutions. The study highlighted two main aspects of needs: objective needs and learning needs. Objectively, the findings indicated that students needed reading, writing, speaking, and listening skills to understand academic texts and communicate in scholarly contexts. From a learning perspective, the findings showed that English instruction needed to be relevant to Islamic studies through an English for Specific Purposes (ESP) approach. The findings suggested that Islamic higher education institutions needed to design contextual and systematic English programs to support the professional development and global competitiveness of prospective PAI teachers.